Testosterone associations with parents’ child abuse risk and at-risk parenting: a multimethod longitudinal examination - Rodriguez, Christina M. (Child maltreatment, 2021)
The current investigation considered salivary testosterone as a potential biomarker of physical child abuse risk. Parents enrolled in a prospective, longitudinal, multimethod study beginning prenatally provided saliva when their toddlers were 18 months old. Mothers and fathers self-reported on their empathy, frustration tolerance, and child abuse risk, as well as completing analog tasks of frustration intolerance and child abuse risk and participating in structured parent-child interactions. In contrast to mothers, fathers' higher testosterone levels were associated with increased child abuse risk, less observed positive parenting, more observed negative parenting, and an analog task of frustration intolerance; such findings were reflected across time. Further, fathers' socioeconomic status moderated the association between testosterone levels and abuse risk. No evidence of partner effects was observed in dyadic analyses. The current findings suggest that higher testosterone levels reflect an increased likelihood that paternal physically abusive behavior may be expressed.